A proof-of-concept for folate-conjugated and quercetin-anchored pluronic mixed micelles as molecularly modulated polymeric carriers for doxorubicin. (15th September 2015) - Hassanzadeh, Salman; Feng, Zhaoxuan; Pettersson, Torbjörn; Hakkarainen, Minna
Abstract: Pluronic, F127 (PEG–PPO–PEG, Mn = 12, 500 g/mol) and reverse pluronic, 10R5 (PPO–PEG–PPO, Mn = 2000 g/mol) were molecularly modulated to reach multifunctional mixed micelle systems aiming to overcome some of the inherent weaknesses of pluronic based drug delivery systems. Targeting function was introduced by covalent attachment of folic acid to F127 (F127-FA), while quercetin was anchored to 10R5 (P-Q). The successful syntheses were evidenced by 1 H NMR, FTIR, DSC and UV–Vis. The proof-of-concept for the mixed micelles prepared from the drug anchored pluronics was demonstrated through reduced CMCs, slower release rates and increased Doxorubicin (DOX) encapsulation capacity from ∼19% to ∼43%. Quercetin therefore boosted the interactions of DOX with the hydrophobic core of the micelles. This was further evidenced by colloidal probe AFM which demonstrated almost doubled adhesion forces between the DOX coated probe and the quercetin modified pluronic as compared to the plain pluronic. The pre-biological essay of the DOX-modulated mixed micelle demonstrates promising properties. In addition quercetin has previously been proposed as combinatory drug to DOX enhancing its therapeutic function and reducing the side effects to normal cells. Graphical abstract: Highlights: Pluronic F127 and 10R5 (reverse blocks) were successfully coupled to folic acid and quercetin. The obtained mixed micelles overcame some inherent weaknesses of pluronic systems. Lower CMC, slower release rates and increased encapsulation capacity was demonstrated. AFM demonstrated doubled adhesion forces between DOX and quercetin modified pluronic.